“The Anger of the Queen Has Gone Forth”: Ilimilku’s Warning to Urtenu in a Ugaritic Piggyback Letter (RS 94.2406 [KTU3 2.88]) - Dewrell, Heath D. (Maarav, 2025)
The present essay begins with a reexamination of a “piggyback” letter from Late Bronze Ugarit, RS 94.2406 (KTU3 2.88), offering a fresh edition of this letter from an unnamed queen of Ugarit to Urtenu that contains a second letter from a certain Ilimilku to the same appended to the end. The edition presented here notes a previously unacknowledged difficulty that, once recognized and accounted for, serves to reveal a degree of tension between the queen of Ugarit and Ilimilku, her scribe. Once properly understood, it becomes clear that Ilimilku’s piggyback letter at the very least recontextualizes the queen’s letter and may well even go so far as to contradict the queen’s instructions outright. The second portion of the essay embarks on a comparison with other analogous piggyback letters from the Late Bronze age, written in both Akkadian and Hittite, to reveal that Ilimilku’s piggyback letter is hardly unique in these regards and that it was not especially uncommon for scribes to append their own letters to those of their patrons, apparently without the latter’s knowledge, often with the goal of advancing the scribes’ own interests and agendas.